DINAMIKA KEBIJAKAN PENGEMBANGAN BIODIESEL BERBAHAN BAKU KELAPA SAWIT INDONESIA - Khoiru Rizqy Rambe; Nunung Kusnadi; Suharno Suharno (Jurnal Sosial Ekonomi Pertanian, 2019)
Indonesia develops palm oil biodiesel driven by mandatory biodiesel which requires the use of biodiesel as a mixture of fuel oil by 30 percent. However, the development of the biodiesel can cause a trade off CPO for the production of biodiesel and palm cooking oil. The purpose of this study is to analyze the achievement of Indonesia's biodiesel production, and formulate policies for the development of the biodiesel industry with consideration of the balance of the food and non-food sectors. The data used are secondary data obtained from various related agencies such as the Central Bureau of Statistics, Ministry of Agriculture, BAPPEBTI, World Bank and other institutions related to this research which are analyzed by dynamic system models. The results of the analysis show that the development of Indonesian biodiesel has not been able to meet the level of the blending rate according to mandatory biodiesel. Efforts to increase the achievement of the blending rate level can be done by providing biodiesel subsidies. Export duty policy is also needed in an effort to maintain the stability of domestic CPO prices and the price of palm cooking oil. The export duty policy in accordance with Minister of Finance Regulation No. 136 of 2015 is more effectively implemented than Minister of Finance Regulation No. 140 of 2016. Keywords : blending rate, dynamic system, mandatory biodiesel,  policy scenario